Esophageal leiomyoma: experience from a single institution. Issue 2 (27th March 2012) - Jiang, W.; Rice, T. W.; Goldblum, J. R.
SUMMARY: Esophageal leiomyomas are rare. We report the clinicopathologic features of one of the largest series of esophageal leiomyomas from a single institution. We retrospectively reviewed the Cleveland Clinic pathology database (1985–2010) for patients with a diagnosis of esophageal leiomyoma(s). Clinicopathologic features of 30 cases from 28 patients were analyzed. The group included 15 females and 13 males with a mean age at diagnosis of 56 years. These include 9 excisions, 9 esophagectomies, and 12 endoscopic biopsies. Only one partial esophagectomy was performed solely for a symptomatic 14‐cm leiomyoma; the remainder of the resections ( n = 8) were for other indications, including esophageal cancer (Barrett's esophagus‐related adenocarcinoma and squamous cell carcinoma) and emergent esophageal perforation, with leiomyoma being an incidental finding. One patient (2.5%) had two synchronous leiomyomas (14 cm and 0.3 cm). Tumor size ranged from 0.1 to 14 cm (mean = 2.0 cm). Mean tumor size among symptomatic patients was 5.2 cm, as compared with 0.4 cm in asymptomatic patients. Dysphagia was the most common complaint in symptomatic patients (71.4%). Sixty‐nine percent of the tumors were located in the distal and middle thirds of the esophagus, with most (69.6%) arising from muscularis propria. Histologically, these tumors were composed of bland spindle cells with low cellularity, no nuclear atypia, or mitotic activity. Only one case (14 cm) showed focal moderate cellularity and nuclear atypia, with low mitotic activity (<1/10 high power field). Immunohistochemical studies showed tumor cells were positive for smooth muscle actin, and negative for CD34 and CD117. Follow‐up information was available for 22 patients (78.6%), and none had adverse events related to leiomyoma. In summary, esophageal leiomyoma is a rare benign tumor of the esophagus. Patients with larger tumors were more likely to have symptoms. The majority of the tumors were in the lower and mid‐esophagus, and arose from muscularis propria. These tumors behave in a clinically benign fashion.